Resilient modulus values of Western Australia asphalt pavement. (October 2019) - Wibisono, G; Nikraz, H R
Abstract: Resilient modulus (MR) is a property to measure the material's stiffness in designing asphalt pavement thickness. The value is usually calculated from an Indirect Tensile Test (ITT) for decades since it is considered efficient and more practical in most applications, and it only uses a single loading time and temperature. The Austroads 2008 still included the resilient modulus values from ITT as an input value at the initial pavement design stage due to its practicality in the application, although this conventional approach has no longer been used in a mechanistic-empirical design guide by NCHRP. In this research, three asphalt mixtures with variables of aggregates diameter and type of asphalt using Western Australia materials were investigated. The mixes, i.e. AC10-320, AC14-320, and AC20-320, were cast in cylinders with a dimension of 75×100mm at a reference temperature of 25°C. The indirect tensile strength used triplicate samples. Research shows the resilient modulus values increase with an increase of nominal maximum aggregate size and a decrease of air voids percentage. The highest MR values were given by mix AC-320 with 3% air voids compared to other mixtures variation. The reasons are an improvement in particle-to-particle contact between the aggregates and density with low air voids in the mixes. From this study, the resilient modulus values of Western Australian asphalt mixtures still meet the lower part of the range of the Austroads presumptive values and recommend as indicative values for design input in pavement thickness calculation.